Revitalizing Customary Law: Reforming Buffalo Farming Practices (Jalangan) in Menaming Village for Sustainable Governance - Ismi, Hayatul; Hasanah, Ulfia; Nofrizal, Nofrizal; Wook, Izawati (Universitas Negeri Semarang, 2024)
This research investigates the revitalization of customary law in buffalo farming practices (Jalangan) in Menaming Village, Rokan Hulu, with the aim of fostering sustainable governance and agriculture. The buffalo farming system in Menaming Village is deeply rooted in traditional practices that combine grazing and caging methods, reflecting the community’s cultural values and environmental stewardship. These practices are designed to minimize the exploitation of natural resources, positioning Rokan Hulu as a region with significant potential to support local livelihoods while contributing to national economic development. The study highlights the vital role of customary law, recognized in Indonesia's Constitution, in maintaining these traditional practices and promoting sustainable livestock management. Key strategies such as converting manure into organic fertilizer, utilizing organic materials for fuel, adopting pesticide-free animal feed, and implementing rotational grazing systems are central to the community's approach. These practices reduce environmental degradation, maintain ecological balance, and enhance livestock health and productivity, all while creating economic benefits, improving farmers’ incomes, and fostering social cohesion. The novelty of this research lies in its demonstration of how customary law can be revitalized and integrated into contemporary governance frameworks to address modern challenges in sustainable agriculture and environmental conservation. This study contributes to the discourse on law reform by proposing that customary law be formally recognized and adapted within Indonesia's legal system as a dynamic tool for promoting sustainable development, empowering local communities, and preserving cultural heritage. The research underscores the urgency of adapting these traditional frameworks to ensure long-term ecological sustainability and community resilience.